Dark Sweet Cherry (Prunus avium) Anthocyanins Suppressed ERK1/2-Akt/mTOR Cell Signaling and Oxidative Stress: Implications for TNBC Growth and Invasion - Ana Carolina Silveira Rabelo; Susanne U. Mertens-Talcott; Boon P. Chew; Giuliana Noratto (Molecules, 2022)
This study aimed to assess dark sweet cherry (DSC) total polyphenols (WE) and anthocyanins (ACN) against metastatic breast cancer (BC). The WE and ACN anticancer activity and underlying mechanisms were assessed in vitro using 4T1 BC cells. A pilot study using a BALB/C mouse syngeneic model bearing 4T1 tumors assessed the anti-metastatic potential of ACN in vivo. ACN inhibited cell viability with higher potency than WE and reduced reactive oxygen species (ROS) (IC50 = 58.6 µg cyanidin 3-glucoside equivalent (C3G)/mL or 122 µM). ACN induced p38 stress-related intrinsic apoptosis, leading to caspase-3 cleavage and total PARP decrease. ACN suppressed ERK1/2 and Akt/mTOR signaling pathways, which are abnormally activated in BC and promote motility and invasion. This was consistent with suppression of VCAM-1 mRNA, Scr phosphorylation and 88.6% reduction of cells migrating to wounded area. The pilot in vivo results supported the ACN-mediated suppression of angiogenesis in tumors and lungs. ACN also lowered Cenpf mRNA in lungs, associated with lung metastasis lesions and poor survival. Results demonstrated the dual Akt-ERK inhibitory role of ACN and suppression of their downstream pro-invasive targets. These results encourage a larger scale in vivo study to confirm that ACN may help to fight BC invasion and metastasis.